Implementasi Algoritma Kriptografi RSA Dalam Aplikasi Sistem Informasi Perpustakaaan - Maria SD. Dairi; Munjiat Setiani Asih; Khairunnisa (LKP Unity Academy, 2023)
The library is an institution or agency that collects printed and recorded knowledge, manages it in a special way to meet the intellectual needs of its users. a library has data that may be known by certain parties, therefore the library must maintain data confidentiality by using security techniques only on its information system. The data security technique used is a cryptographic algorithm, which is a technique for converting data into certain codes so that the stored information cannot be read by anyone except the authorized person. The RSA cryptographic algorithm used is the RSA cryptographic algorithm. The RSA algorithm was created by 3 researchers from MIT (Massachussets Institute of Technology) in 1976, namely: Ron (R)ivest, Adi (S)hamir and Leonard (A)dleman. The security of the RSA algorithm lies in the difficulty of factoring large numbers into prime factors. In the RSA cryptographic algorithm, there are three processes, namely the process of generating public and private keys, the encryption process, and the decryption process.